Dr Fanon on colonial narcissism and anti-colonial melancholia - Wright, Colin (Palgrave Macmillan, 2017)
This chapter provides an outline of Fanon’s involvement in the most progressive strand of French psychiatry that became known as ‘psychothérapie institutionnelle’, as well as of his clinical response to the colonial context at the Bilda-Joinville hospital in Algeria, in order to demonstrate the strong continuities between his psychiatric practice on the one hand, and his critical writings and political activism on the other. This brief portrait of ‘Dr Fanon’ paves the way for a discussion of the impact of the Freudian concepts of narcissism and melancholia on his two best known works, Black Skin, White Masks and The Wretched of the Earth. I argue that through his critical (re)deployments of narcissism and melancholia, Dr Fanon controversially comes to prescribe revolutionary violence and the creation of a new militant national community as a means of ‘treatment’ for subjective yet always also social ailments.